AN EXAMINATION OF THE RELATIONSHIP BETWEEN INFLATION AND ECONOMIC GROWTH IN G-7 COUNTRIES WITH THE SECOND GENERATION PANEL CAUSALITY TEST (Third Sector Social Economic Review, 2024)
This study aims to analyse the causality relationship between economic growth and inflation and the direction of this relationship in the period 1994-2023 in G-7 countries. Inflation is an important macro indicator that economies have to cope with. It has recently become an important problem in world economies, especially due to global events such as pandemics, supply chain disruptions, energy crises and geopolitical tensions. Economic growth, on the other hand, constitutes one of the primary goals of economies. In this context, this study investigates the causality relationship between these two important macro indicators in developed countries. In this context, Konya (2006) test, which is a second generation causality test, was utilised. According to the findings, a unidirectional causality relationship was found from growth to inflation at the panel level. However, country-by-country analyses reveal that the causality relationship from growth to inflation is significant only in Canada and France, while no significant relationship is found in other countries. On the other hand, when the causality from inflation to growth was analysed, a significant relationship was found at the panel level; however, this time, unidirectional causality was found only for France. This reveals the existence of bidirectional causality between growth and inflation in France. The results suggest that the relationship between growth and inflation may exhibit structural differences across G-7 countries and this may be due to factors such as cost inflation, monetary policies, demand structure and supply shocks. In line with the findings, the study suggests policy recommendations for G-7 countries to maintain the balance between inflation and growth targets.
Keywords: Inflation; Economic Growth; G-7 Countries; Causality Relationship; Second Generation Panel Causality Test